Kinetics study of the Al–water reaction promoted by an ultrasonically prepared Al(OH)3 suspension. Issue 42 (11th April 2016) - Liang, Gao-Heng; Gai, Wei-Zhuo; Deng, Zhen-Yan; Xu, Pingguang; Cheng, Zhenxiang
Abstract : The hydrogen-generation rate of Al in a Al(OH)3 suspension is comparable to the behavior of Al in a NaOH solution. Abstract : The kinetics of the Al–water reaction promoted by an ultrasonically prepared Al(OH)3 suspension is investigated. It is found that the induction time for the beginning of the Al–water reaction decreases and the reaction rate increases with increasing suspension concentration, volume, and temperature, because the Al–water reaction is exothermic. When the weight ratio of Al to water increases to 1 : 15, there is almost no induction time, and more than 80% of Al in the Al(OH)3 suspension is consumed within 40 min, which is comparable to the behavior of Al in NaOH solution. A collision model based on Brownian motion is proposed to analyze the reaction process, which shows that the contact between Al and Al(OH)3 particles and the reaction heat are two key factors that control the reaction progress.